1998
DOI: 10.1046/j.1432-1327.1998.2580854.x
|View full text |Cite
|
Sign up to set email alerts
|

The roles of the N‐linked glycans and extension regions of soybean β‐conglycinin in folding, assembly and structural features

Abstract: β-Conglycinin, one of the dominant storage proteins of soybean, is a trimer composed of three subunits, A, A′ and β. All subunits are N-glycosylated and A and A′ contain extension regions in addition to the core regions common to all subunits. Non-glycosylated individual subunits and deletion mutants (A c and A′ c ) lacking the extension regions of A and A′ were expressed in Escherichia coli. All recombinant proteins were purified to near homogeneity and appeared to have the correct conformation, as judged by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
226
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 180 publications
(238 citation statements)
references
References 35 publications
10
226
2
Order By: Relevance
“…More than 20 allergenic proteins with IgE-binding activity have been identified in soybeans (Babiker et al, 1998), and both soybean 7S and 11S have been identified as soybean allergens (Maruyama et al, 1998). In this study, most components of 7S and 11S could be degraded.…”
Section: Discussionmentioning
confidence: 75%
“…More than 20 allergenic proteins with IgE-binding activity have been identified in soybeans (Babiker et al, 1998), and both soybean 7S and 11S have been identified as soybean allergens (Maruyama et al, 1998). In this study, most components of 7S and 11S could be degraded.…”
Section: Discussionmentioning
confidence: 75%
“…β-conglycinin is a major component of 7S globulin in soybean, and is a trimer with a molecular weight of 150 kDa (Hill and Breidenbach, 1974) and is composed of three subunits: α' (76 kDa), α (72 kDa), and β (52-54 kDa) (Fontes et al, 1984). It shows high similarity in the domain area of each domain, being 90.4% between subunits α and α', 76.2% between α and β, and 75.5% between subunits α' and β (Maruyama et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…β-Conglycinin has the trimeric structure common to 7S globulins of other plant species and is composed of three subunits, α, α' and β. The α and α' subunits contain an N-terminal extension in addition to a core region common to all the subunits (Maruyama et al, 1998(Maruyama et al, , 2001. The β subunit consists of only the core domain.…”
Section: Introductionmentioning
confidence: 99%